Uji Efektivitas Ekoenzim Kulit buah Naga ( Hylocereus polyrhizus ) Dalam Menekan pertumbuhan Bakteri Staphylococcus aureus - Dwi Ambarwati, Dinda; Marmaini, Marmaini (Indobiosains, 2025)
The study entitled The Effectiveness of Dragon Fruit Peel Ecoenzyme in Suppressing the Growth of Staphylococcus aureus Bacteria was conducted on May 8-9, 2025, at the Center for Public Health Laboratory of South Sumatra Province. The method used in the antibacterial test was the disc diffusion method. This study aimed to evaluate the effectiveness of ecoenzyme from dragon fruit peel (Hylocereus spp.) in suppressing the growth of Staphylococcus aureus bacteria, the cause of infection in humans. Ecoenzyme was made with the addition of EM4 to accelerate the fermentation process. Antibacterial activity tests were carried out using the disc diffusion method on NA agar media. The test results showed that dragon fruit peel ecoenzyme did not form an inhibition zone against the growth of Staphylococcus aureus at various concentrations tested. This finding indicates that the ecoenzyme does not have significant antibacterial ability against this gram-positive bacteria. This may be due to the low content of active antimicrobial compounds in the ecoenzyme, or because of the natural resistance of Staphylococcus aureus to the compounds contained in the ecoenzyme.